(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
In review of Indian administrative structure in 1950s, Appleby certified Indian Civil Service to be one of the best in the world. While there is still a lot to commend the civil service for, this article will focus exclusively on the deficiencies that have crept in the services over last few years. This should not be taken to mean that all is wrong with it. The article does, however, attempt to present the critique of the service from the perspective of an insider with a view to rid it of its malaise. Despite its notable achievements, over last five decades, disenchantment with public administration in India has dramatically increased.Few aspects of economic policy elicit more conflicting opinions than the role of bureaucracy in policy making and implementation. These range from Max Weber’s picture of a rule-governed efficient institution, to the "Yes, Minister" caricature of one bound in complex red tape, operating inefficiently and serving the interests of its own officials. In this lecture I attempt a better understanding guided by the economics of incentives and organizations. I emphasize the multidimensional complexity of government bureaucracies - they are answerable to multiple political principals, must handle multiple tasks, have multiple levels of hierarchy, and so on - and suggest some institutional and organizational reforms that seem relevant for India and other less-developed countries that wish to sustain growth and progress to and beyond a middle-income level.One central function of bureaucracies is to determine eligibility in many federal and state programs. The structure of the organization in which decisions are made may affect whether the organization has a predisposition to be more lenient or more stringent in eligibility determinations. In this paper I compare the determinants of eligibility decisions in Social Security Disability across two different bureaus within the Social Security Administration (Administrative Law Judge offices and state government Disability Determination Services). I test the hypothesis that structural differences between the two units explain why each unit responds differently to signals from the environment, to the ability to gather information, and to cognitive biases created from the ideological environment where decisions are made.